Characterization and pathogenicity of Fusarium spp. isolates causing root and collar rot on carrot. Issue 1 (2nd January 2023) - Pascouau, Claire; Chateau, Corentin; Bastide, Franck; le MOULLEC-RIEU, THOMAS; Guillemette, Thomas; Hamon, Bruno; Aligon, Sophie; Cailleau, Agathe; Sochard, Daniel; Gombert, Julie; Morel, Elise; Laurent, Emmanuelle; et al.
Abstract: Since 2015, necrosis caused by Fusarium spp. has been regularly observed in carrot seed crops in France. A collection of 53 Fusarium isolates was gathered from lesions on carrot between 2016 and 2019. Morphological characterization at both the macroscopic and microscopic levels and molecular typing based on the ACL1, RPB2 and EF1-α partial gene sequences resulted in the identification of two main groups, corresponding to 22  F. avenaceum and 22  F. tricinctum isolates. In addition, three isolates of F. graminearum, two each of F. oxysporum and F. acuminatum, and one isolate of F. solani were also identified. Dual cultures of Trichoderma spp. ( T. atroviride and T. harzianum ) and Fusarium spp. ( F. tricinctum isolate FT001 and F. avenaceum isolate FA002) did not indicate any antibiosis capabilities of Trichoderma . The in vitro sensitivity of isolates FT001 and FA002 to two fungicides and one natural product was similar, with an efficacy depending on the active ingredient. Prothioconazole + tebuconazole was more effective (mycelial growth reduced by 97% for FT001 and 99.8% for FA002) than fluopyram + trifloxystrobin (mycelial growth reduced by 58% and 56%, respectively). Allium extracts seemed to be a promising alternative to fungicides, since they were almost as efficient as prothioconazole + tebuconazole. Artificial inoculation of durum wheat using three isolates from carrot lesions (FT001, FA002 and F. graminearum FG001) induced plant necrosis. This result suggests that Fusarium pathogens of carrot seed crops may be transmitted to wheat, which is commonly used in rotation with carrot.